KINERJA DINAS PENGENDALIAN PENDUDUK, KELUARGA BERENCANA, PEMBERDAYAAN PEREMPUAN, DAN PERLINDUNGAN ANAK TERHADAP KASUS KEKERASAN ANAK MELALUI PROGRAM BKB (BINA KELUARGA BALITA) DI KABUPATEN BADUNG - Agrevina, Elsa; Wirantari, I Dewa Ayu Putri; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2023)
Violence is something that we often encounter in social life and what we most often encounter is violence that occurs in the family environment, especially acts of violence against children, both in the form of verbal violence and physical violence. In this case, Badung Regency has a work program that is planned to prevent and suppress the increasing number of cases of violence, namely the BKB (Toddler Family Development) Program carried out by the Office of Population Control, Family Planning, Women's Empowerment, and Child Protection. The type of research that the writer uses is descriptive qualitative writing. In this study the authors used research indicators proposed by Agus Dwiyanto (2006:50-51), namely Productivity, Service Quality, Responsiveness, Responsibility, and Accountability.